Evolution, Recent Progress and Perspectives of the Seismic Monitoring of Building Structures in Romania - Tiganescu, Alexandru; Craifaleanu, Iolanda-Gabriela; Aldea, Alexandru; Grecu, Bogdan; Vacareanu, Radu; Toma-Danila, Dragos; Balan, Stefan-Florin; Dragomir, Claudiu-Sorin (Frontiers in Earth Science, 2022)
The seismic instrumentation of structures in order to assess their condition and to track it over long periods or after representative events has proven to be a topic of large interest, under continuous development at international level. The seismic hazard of Romania poses one of the most dangerous threats for the country, in terms of potential physical and socio-economic losses. In recent years, taking advantage of the new scientific and technological advances, among which the exponential growth in computational resources, significant improvements have been made in extending the seismic networks for structural monitoring and using the data as input for products and services addressed not only to the research community but also to stakeholders. The paper covers focused aspects of the topic for Romania, referring to past developments of the most important institutions and seismic networks in the country and the current status, including the research and regulatory gaps. Currently, three main research and academic institutions perform structural health monitoring of twenty-two buildings in Romania. As the number of monitored buildings grows and new actors in the private sector start to get involved in the process, the need for data standardization and a regulatory framework increases. Ongoing national and international projects (PREVENT, SETTING, TURNkey) address these issues and outline the roadmap for future actions of the main institutions responsible for seismic risk reduction, including authorities, research and academia.